Synbiotics reduce ethanol-induced hepatic steatosis and inflammation by improving intestinal permeability and microbiota in rats. Issue 5 (13th May 2015) - Chiu, Wan-Chun; Huang, Ya-Li; Chen, Ya-Ling; Peng, Hsiang-Chi; Liao, Wei-Hsiang; Chuang, Hsiao-Li; Chen, Jiun-Rong; Yang, Suh-Ching
<x xml:space="preserve">Abstract</x> Clinical and animal experiments indicated that gut-derived endotoxin and imbalanced intestinal microbiota contribute to the pathogenesis of alcoholic liver disease (ALD).